Pengaruh Jalan Tol Terhadap Pembangunan Ekonomi Khususnya UMKM di Sumatera Utara - Muhammad Dzaki Abdillah; Isnaini Harahap; Windu Anggara; Siti Nurojiyah (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
Roads play a crucial role in economic development, especially for Micro, Small, and Medium Enterprises (MSMEs). In North Sumatra, the rapid development of toll roads has significantly impacted the accessibility and efficiency of goods and services distribution. This study aims to analyze the influence of toll road development on the growth of MSMEs in the region. Utilizing statistical data and case studies, this research demonstrates that infrastructure improvements contribute to local economic growth and enhance the competitiveness of MSMEs.